Skrining Bakteri Lipolitik Pendegradasi Polystrene (PS) dari TPU Bonoloyo, TPS Makam Haji, dan Aliran Sungai Bengawan Solo - Halim, Ilham Surya; Rahayu, Triastuti (Bioscientist : Jurnal Ilmiah Biologi, 2024)
Waste is an environmental problem caused by the activities of living things. The synthetic waste group or what is often found in the form of plastic and the like is a group of waste that is very difficult to degrade. This can be overcome by using lipolytic bacteria. This research aims to analyze lipolytic bacteria which can be used to biodegrade plastic waste in the Bonoloyo TPU, Makam Haji TPS, and the Bengawan Solo river flow. This research uses quantitative descriptive methods. Screening for lipolytic bacteria degrading polystyrene (PS) showed that the highest population of lipolytic bacteria isolated from public burial places of 15.6 x 104. Meanwhile, lipolytic screening with the highest average clear zone formed was 0.641 cm which came from TPS 1, then average -The highest average lipolytic index came from SBS 2 with a figure of 1.6525 cm, the largest average colony diameter came from TPS 1 soil samples at 0.45 cm. The degradative nature of bacteria on plastic above shows that the Bengawan Solo river has microbes with the highest ability compared to microbes from TPS and TPU, namely 22.42%. The degradation between TPU, SBS, and TPS is significantly the same. PS degradation in Bonoloyo TPU shows significant physical changes.